Sukuk’s role in financing infrastructural development during the covid-19 pandemic in Nigeria - Usman, Abubakar Abubakar; Sa'ad, Auwal Adam (Springer, 2023)
The Covid-19 pandemic has affected the financing infrastructural devel- opment particularly in the Global South (GS). Amid the pandemic, Nigeria has found sukuk financing as an alternative source for financing some of its infrastruc- tural development. This article aims at investigating why sukuk offers a significant alternative source of financing infrastructural development in Nigeria. The article argues that the lack of availability of conventional sources of financing development, economic downturn caused by Covid-19, the potential investment return, the sukuk structure, and sukuk successes in other economies all contribute to the sukuk thriving as an important alternative source of financing infrastructural development in Nigeria.